2018
DOI: 10.3389/fnins.2018.00567
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Tetramethylpyrazine Derivative Protects Against Glutamate-Induced Cytotoxicity Through PGC1α/Nrf2 and PI3K/Akt Signaling Pathways

Abstract: Glutamate-induced excitotoxicity is one of the main causes of neuronal cell death in stroke. Compound 22a has been previously reported as a promising neuroprotective compound derived from tetramethylpyrazine, which is a widely used active ingredient of traditional Chinese medicine Chuanxiong (Ligusticum wallichii Franchat). Compound 22a can protect neurons from oxidative stress-induced PC12 cell death and alleviates the infarct areas and brain edema in a rat permanent middle cerebral artery occlusion model. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 44 publications
(52 reference statements)
1
19
0
Order By: Relevance
“…Many studies have shown that TMP and its derivatives or compatibility with salvianic acid A/resveratrol possess functional cardioprotection/neuroprotection after myocardial ischemia-reperfusion/ischaemic stroke through interfering with PI3K/Akt/GSK3 β , PGC1 α /Nrf2, BDNF/Akt/CREB pathway, up-regulating Nrf-2 and HO-1 expression, maintaining Ca 2+ homeostasis, and inhibiting inflammatory reaction, etc. [1820, 5052]. Some researchers have shown that TMP and prescriptions as mentioned above can attenuate injury Dox-induced cardiotoxicity and nephrotoxicity by inhibiting oxidative stress, cell autophagy and apoptosis [53, 54].…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have shown that TMP and its derivatives or compatibility with salvianic acid A/resveratrol possess functional cardioprotection/neuroprotection after myocardial ischemia-reperfusion/ischaemic stroke through interfering with PI3K/Akt/GSK3 β , PGC1 α /Nrf2, BDNF/Akt/CREB pathway, up-regulating Nrf-2 and HO-1 expression, maintaining Ca 2+ homeostasis, and inhibiting inflammatory reaction, etc. [1820, 5052]. Some researchers have shown that TMP and prescriptions as mentioned above can attenuate injury Dox-induced cardiotoxicity and nephrotoxicity by inhibiting oxidative stress, cell autophagy and apoptosis [53, 54].…”
Section: Discussionmentioning
confidence: 99%
“…Ligustrazine is one of the main biologically active components known from the traditional Chinese medicine Chuanxiong (Ligusticum wallichii Franchat), widely used for the clinical treatment of cardiovascular diseases, [95][96][97] and has pronounced antitumor 98 and neuroprotective properties. [99][100][101] Numerous series of derivatives have been synthesized on the basis of ligustrazine including dimeric ones. 100,102,103 The patent 94 describes in detail the synthesis of bivalent compounds based on ligustrazine and securinine (Scheme 15) with the preliminary production of 2,5-bis(bromomethyl)-3,6dimethylpyrazine and aminosecurinine followed by their combination into a bivalent derivative.…”
Section: Bivalent Securinine Analoguesmentioning
confidence: 99%
“…Glutamate-induced cytotoxicity is one of the leading causes of neuronal cell death. 35 In this study, we rst compared the cytotoxicity among different neural cells. The cell viability experiment was performed to four typical neural cells, including PC22, SH-SY5Y, HT22 and primary astrocytes.…”
Section: Glutamate Induced Cell Viability Assay On Various Neural Cellsmentioning
confidence: 99%